Political Spectacle and the Fate of American Schools. - Smith, Mary Lee (Critical Social Thought Ser., 2003)
The authors argue that the most influential and well-known educational policy programs in the past 30 years are not based on democratic consensus, but are instead formulated by the political community as symbolic efforts meant to generate personal.